Eccentric decline squat protocol offers superior results at 12 months compared with traditional eccentric protocol for patellar tendinopathy in volleyball players - Young, M. A.; Cook, J. L.; Purdam, C. R.; Kiss, Z. S.; Alfredson, H. (British Journal of Sports Medicine, 2005)
Background: Conservative treatment of patellar tendinopathy has been minimally investigated. Effective validated treatment protocols are required.